Do different surgical techniques in tibia pilon fractures change the results of the midterm? - BİÇİCİ, Vedat (Turk J Med Sci, 2020)
BACKGROUND/AIM: Pilon fracture is difficult to treat fractures due to many complications that can develop after surgery. To achieve the best results, different surgical approaches are used.In our study, we aimed to compare the functional results and complication rates of our treatments in patients treated with 3 different surgical tecniques. MATERIALS AND METHODS: 89 pilon fractures of 87 patients treated for pilon fracture were evaluated. Patients were examined in 3 different groups (one step, two step surgery and Ilizarov). Functional results, postoperative complications and ankle AOFAS scores were evaluated. RESULTS: The mean AOFAS score of the all patients was 77.67. There was no significant difference between 3 surgical techniques (P = 0,880). While skin complication was not seen in patients who underwent double-stage surgery and Ilizarov (0%); It was seen in 6 (15.7%) patients who underwent single-stage surgery. Treatment results were found to be better in type 1 and type 2 fractures, while in type 3 fractures (P = 0.004). CONCLUSION: Despite the different surgical approaches and implants applied, no difference was found between the midterm ankle functional results of the patients. Two-stage surgery and Ilizarov is a safe and effective treatment approach to reduce morbidity and early complications in pilon fractures.